Detection of SARS-CoV-2 in Wastewater at Residential College, Maine, USA, August–November 2020 - Yolanda M. Brooks (Centers for Disease Control and Prevention, 2021)
We used wastewater surveillance to identify 2 coronavirus disease outbreaks at a college in Maine, USA. Cumulative increases of >1 log10 severe acute respiratory syndrome coronavirus 2 RNA in consecutive 24-hour composite samples preceded the outbreaks. For 76% of cases, RNA was identified in grab samples from residence halls <7 days before case discovery.